1992
DOI: 10.1177/153857449202600606
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostacyclin on Heparin Reversal with Protamine

Abstract: This study was planned to show the beneficial effects of prostacyclin (PGI2) utilization on adverse effects of protamine. PGI2 was administered at a rate of 5 ng/kg/min. Twenty patients entered this study. Half of them received PGI2 whereas the others did not. Right ventricular end-diastolic volume index and right ventricular stroke work index were 72 mL/m2 and 2.2 g.m/m2, respectively, after patients were weaned off the bypass and 79 and 1.5, respectively, at five minutes after pro tamine administration in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In previous studies, it was shown that aminophylline and prostacyclin protected the heart from protamine cardiotoxicity by elevating the cAMP level. 14,15 The most marked effects of aminophylline were observed during the early reperfusion period in terms of volume-pressure relationship and myocardial metabolism. In group 2 under maximal volume loading conditions, there was better contractile activity, increased oxidative activity, and less lactate release compared with the other groups, indicating reduced injury.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, it was shown that aminophylline and prostacyclin protected the heart from protamine cardiotoxicity by elevating the cAMP level. 14,15 The most marked effects of aminophylline were observed during the early reperfusion period in terms of volume-pressure relationship and myocardial metabolism. In group 2 under maximal volume loading conditions, there was better contractile activity, increased oxidative activity, and less lactate release compared with the other groups, indicating reduced injury.…”
Section: Discussionmentioning
confidence: 99%